The Influence Of Environmental Awareness And Price On Purchase Intention Through Brand Image Mediated By Age Factor On Sukkhacitta Products - Hari Sel, Boby Jamis; Madiawati, Putu Nina; Pradana, Mahir (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
This study analyzes the influence of environmental awareness and price on purchase intention, mediated by brand image and moderated by age, within the context of sustainable fashion products, specifically the Sukkhacitta brand, among consumers in Bandung, Indonesia. Employing a quantitative approach, data were collected from 384 respondents through structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that both environmental awareness and price exert significant direct effects on purchase intention, with brand image serving as a partial mediator in these relationships. Furthermore, age acts as a significant moderator, strengthening the impact of brand image and price on purchase intention, while slightly weakening the effect of environmental awareness. The study also highlights that environmental awareness and price are perceived positively by consumers, yet emotional connection and brand loyalty remain areas for improvement. Importance-Performance Map Analysis (IPMA) underscores the critical role of age and price in shaping purchase intention, suggesting that tailored marketing strategies based on age segmentation can enhance consumer engagement. The research contributes to the literature by integrating age as a moderator in the sustainable fashion context and provides actionable insights for practitioners seeking to optimize marketing strategies for eco-friendly products. The study’s implications extend to both academia and industry, emphasizing the need for transparent communication of sustainability values, competitive pricing, and targeted brand positioning to foster stronger purchase intentions among diverse consumer segments.